An electroamalgamation approach to separate 47Sc from neutron-activated 46Ca target for use in cancer theranostics. Issue 14 (22nd September 2017) - Chakravarty, Rubel; Chakraborty, Sudipta; Ram, Ramu; Dash, Ashutosh
ABSTRACT: Scandium-47 [T½ = 3.35 d, Eβ- (max.) = 600 keV, Eγ = 159 keV] is a relatively new radioisotope that holds tremendous potential for use in cancer theranostics. The radioisotope was produced by thermal neutron irradiation of enriched 46 Ca producing 47 Ca, which decays by β − emission to 47 Sc. A viable method based on the selective electroamalgamation of Ca 2+ ions has been developed for the clinical-scale separation of 47 Sc from 47 Ca. The overall yield of 47 Sc after the separation process was >80% and it was obtained with >99.9% radionuclidic purity in a form suitable for radiopharmaceutical preparation. This strategy holds promise for future clinical translation of this radioisotope.